2019
DOI: 10.1088/1742-6596/1294/2/022012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding BaTiO3 to PVDF as Nano Generator

Abstract: Piezoelectric nanogenerator based on a composite structure formed of Polyvinylidene Fluoride (PVDF) as the matrix and Barium Titanate BaTiO3 nanospherical after dissolving them in a solvent of Dimethyl Sulfoxide DMSO/Acetone in (1/3 v/v) then spanning it’s homogeneous solution on Aluminum foil. structural and morphology analyses that of fabricated nanofibers characterized by X-ray diffraction, Scanning Electron Microscope and the electrical output of piezoelectric membrane devices was measured by using oscillo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Primarily, the technique used in our synthesis was electrospinning, which enables in situ poling and is relatively easier for the formation of the β-phase with the highest fraction. Compared to this, PVDF-BT composites synthesized via solvent casting and nanoimprinting processes could generate a higher voltage only when it is subjected to high pressure. , Among ES PVDF-BT composites in the table, our device could achieve a higher voltage of ∼50 V from a small PENG device by applying a meager force of ∼3 N, which is the lowest considering the quantum of voltage generated. This promising result stems from the proper optimization of electrospinning parameters, which makes the fraction of the β-phase higher , and also facilitates the meticulous design of the device.…”
Section: Resultsmentioning
confidence: 87%
“…Primarily, the technique used in our synthesis was electrospinning, which enables in situ poling and is relatively easier for the formation of the β-phase with the highest fraction. Compared to this, PVDF-BT composites synthesized via solvent casting and nanoimprinting processes could generate a higher voltage only when it is subjected to high pressure. , Among ES PVDF-BT composites in the table, our device could achieve a higher voltage of ∼50 V from a small PENG device by applying a meager force of ∼3 N, which is the lowest considering the quantum of voltage generated. This promising result stems from the proper optimization of electrospinning parameters, which makes the fraction of the β-phase higher , and also facilitates the meticulous design of the device.…”
Section: Resultsmentioning
confidence: 87%
“…The amount of BT was between 0.4 and 0.8 wt.%. On the other hand, a DMSO/acetone solvent mixture was used with a higher BT (20 and 25%) powder to prepare a PVDF film by Hussein et al [ 102 ]. This work demonstrated that the addition of BT to the electrospinning process of PVDF promoted β-phase crystallization over α-phase.…”
Section: Additives To Improve Piezoelectric Properties Of Electrosmentioning
confidence: 99%
“…The formation of desired β-phase PVDF was shown with a sample of 3 wt.% BT addition. Moreover, the capacitance increased significantly for BT/PVDF samples compared to pure PVDF [ 102 ].…”
Section: Additives To Improve Piezoelectric Properties Of Electrosmentioning
confidence: 99%
“…11 As piezoelectric nanocomposites obtained via electrospinning provide a large piezoelectric coefficient and excellent flexibility, flexible piezoelectric pressure sensors based on PVDF nanocomposites obtained from electrospinning have a great potential for the wearable devices by achieving the efficient conversion between mechanical energy and electrical energy. Recently, Hussein et al 17 fabricated a piezoelectric nanogenerator based on a composite structure formed of PVDF as the matrix and BaTiO 3 nanospheres. Yaqoob et al 18 used a method of spray coating to prepare a trilayer flexible piezoelectric nanogenerator based on surface-modified graphene and PVDF-BaTiO 3 nanocomposites.…”
Section: Introductionmentioning
confidence: 99%